2019
DOI: 10.5187/jast.2019.61.5.294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin levels on physiological responses, blood profiles, and reproductive performance in gestating sows

Abstract: This study was performed to evaluate the effects of dietary vitamin levels on physiological responses, blood profiles, and reproductive performance in gestating sows. A total of 52 F1 multiparous sows (Yorkshire × Landrace) with an average body weight of 223.5 ± 31.7 kg, an average parity of 6.4 ± 2.7, and an average backfat thickness of 18.5 ± 4.9 mm were divided into four treatment groups considering body weight, backfat thickness, and parity in a completely randomized design with 13 replicates. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Hence, several biological factors could jointly affect serum concentration. As seen in previous reports, evidence has also shown that blood concentration is not only influenced by dietary levels but metabolic Ca demand as well [40,41]. Studies have shown that during lactation, available Ca and P are often elevated.…”
Section: (Oh)d3supporting
confidence: 57%
“…Hence, several biological factors could jointly affect serum concentration. As seen in previous reports, evidence has also shown that blood concentration is not only influenced by dietary levels but metabolic Ca demand as well [40,41]. Studies have shown that during lactation, available Ca and P are often elevated.…”
Section: (Oh)d3supporting
confidence: 57%
“…These results are attributed to the mechanism of the direct action of vitamin 1,25-(OH) 2 D 3 on the homeostasis of calcium and phosphorus, minerals that are associated with uterine contraction [19]. Blim et al [5] found an increased calcium level at the onset of the fetal expulsion stage.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, vitamin 1,25-(OH) 2 D 3 has a potential physiological role in the regulation of immune responses, along with the vitamin D receptor, which is induced after the activation of pathogen recognition receptors and can induce the synthesis of antibacterial proteins [38], which promotes improvements in the general health of animals through various nongenomic mechanisms, such as protein expression, inflammation, oxidative stress, and cellular metabolism [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most producers provide these vitamins close to the requirements, and they observed optimum growth under commercial feeding conditions. Previous studies reported that high levels of dietary supplementation of B vitamins could not improve performance, and NRC levels for pigs are sufficient to meet their needs [ 19 , 20 ]. A similar situation was described in a survey carried out in the United States [ 15 ], where some producers do not include thiamine, vitamin B 6 , folic acid, and choline (mainly for growing–finishing pigs).…”
Section: Discussionmentioning
confidence: 99%